PENGARUH INDEPENDENSI, KOMPETENSI, INTEGRITAS AUDITOR INTERNAL DAN EFEKTIFITAS PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN AUDIT INTERNAL (Studi Kasus Pada Perum Percetakan Uang RI) - Edi Wibowo (Universitas Mercu Buana, 2016)
This study aims to examine the impact of independency, competence, integrity, and internal control corporate to the quality of audit result of auditor internal Satuan Pengawasan Intern using multiple regression analysis . The object of this study is internal auditor the Indonesian Security Printing and Minting corporation. This study is an empirical study with purposive sampling techniques of data collection quesionery. Respondents in this study are the 60 auditor and ex auditor internal in Perum Percetakan Uang RI. There are 5 variables in this research that consist of four independent variables namely experience, independency, competence, integrity, and internal control corporate and one dependent variable that is the quality of audit result. According to the results of research, it can be concluded that independency and integrity internal control significantly affect the quality of audit result, while comptence and internal control did not significantly affect the quality of audit result. The coefficient of determination indicates that the independency, competence, integrity and internal control simultaneously affect the dependent variable (the quality of audit result) of 78,30%, while the remaining 22.70% influenced by other factors